Multiple regulation by external ATP of nifedipine-insensitive, high voltage-activated Ca(2+) current in guinea-pig mesenteric terminal arteriole - Morita, Hiromitsu (Blackwell Science Inc, 2002)
We investigated the receptor-mediated regulation of nifedipine-insensitive, high voltage-activated Ca(2+) currents in guinea-pig terminal mesenteric arterioles (I(mVDCC)) using the whole-cell clamp technique. Screening of various vasoactive substances revealed that ATP, histamine and substance P exert modulatory effects on I(mVDCC). The effects of ATP on I(mVDCC) after complete P2X receptor desensitization exhibited a complex concentration dependence. With 5 mm Ba(2+), ATP potentiated I(mVDCC) at low concentrations (∼1–100 μm), but inhibited it at higher concentrations (>100 μm). The potentiating effects of ATP were abolished by suramin (100 μm) and PPADS (10 μm) and by intracellular application of GDPβS (500 μm), whereas a substantial part of I(mVDCC) inhibition by milimolar concentrations of ATP remained unaffected; due probably to its divalent cation chelating actions. In divalent cation-free solution, I(mVDCC) was enlarged and underwent biphasic effects by ATPγS and ADP, while 2-methylthio ATP (2MeSATP) exerted only inhibition, and pyrimidines such as UTP and UDP were ineffective. ATP-induced I(mVDCC) potentiation was selectively inhibited by anti-Gα(s) antibodies or protein kinase A (PKA) inhibitory peptides and mimicked by dibutyryl cAMP. In contrast, ATP-induced inhibition was selectively inhibited by Gα(q/11) antibodies or protein kinase C (PKC) inhibitory peptides and mimicked by PDBu. Pretreatment with pertussis toxin was ineffective. The apparent efficacy for I(mVDCC) potentiation with PKC inhibitors was: ATPγS > ATP≥ADP and for inhibition with PKA inhibitors was: 2MeSATP > ATPγS > ATP > ADP. Neither I(mVDCC) potentiation nor inhibition showed voltage dependence. These results suggest that I(mVDCC) is multi-phasically regulated by external ATP via P2Y(11)-resembling receptor/G(s)/PKA pathway, P2Y(1)-like receptor/G(q/11)/PKC pathway, and metal chelation.